ANALYSIS OF THE SUSTAINABILITY OF THE AQIQAH BUSINESS “GRUP TERNAK KITA” AMIDST MODERN MARKETING COMPETITION - Sinta Suci Lestari; Jojo Jojo; Gugyh Susandy; Devy Widya Apriandi; Asep Kurniawan; Mutqi Sopiawadi (JASS (Journal of Accounting for Sustainable Society), 2025)
This research discusses the sustainability of business "Aqiqah Grup Ternak Kita" modern marketing competition. This business plays a vital role in supporting the local economy and empowering farmers and micro-entrepreneurs in the agribusiness sector. Using a qualitative descriptive method, the research examinese conomic,social,and environmental aspects,as well as the digital marketing strategie simplemented. The results indicate that service innovation,product quality improvement,and marketing digitalization support business sustainability,although still facing challenges in technological resources,price competition,and consumer preference changes.